Education 3590. Moral education. No. 08. Interview with Dr. Mulholland - Magsino, Romulo F. (Teacher)
Dr. Romulo Magsino interviews Dr. Leslie Mulholland on the topic of ethics. An ETV production.; Begins abruptly Tracking poor in places.